Myasthenia Crisis Vs Cholinergic Crisis: Challenges in Crisis Management Without Plasmapheresis or Intravenous Immunoglobulin (IVIG) - Lila Tri Harjana; Hardiono Hardiono (Faculty of Medicine-Universitas Airlangga, 2020)
Introduction: Myasthenia gravis (MG) is an acquired autoimmune disorder clinically characterized by skeletal muscle weakness & fatigability on exertion with prevalence as high as 2–7 in 10,000 and women are affected more frequently than men ( 3:2). Over 12-16% of generalized MG patients experience crisis once in their lifetime. A serious complication of myasthenia gravis is respiratory failure. This may be secondary to an exacerbation of myasthenia (myasthenia crisis) or to treatment with excess doses of a cholinesterase inhibitor (cholinergic crisis). Case Report: Thirty-two years old woman refereed from a private hospital to ED for further treatment with myasthenia in crisis, after nine days of treatment in the previous ICU. Patient already in intubation with mechanical ventilation and history of the treatment of a high dose of multiple anticholinesterase drugs and steroids without plasmapheresis or immunoglobulin intravenous. During admission, diarrhea was present, with no sign of GI infection. On the third day of admission, the patient performed a Spontaneous Breathing Trial and was a success then extubated. Then two day after extubation, the patient falls to respiratory failure and need mechanical ventilation. Anticholinesterase test was performed, and it shows no improvement in clinical signs, and diagnose as Cholinergic Crisis. After re-adjustment of anticholinesterase drug with a lower dose, clinically, the respiratory condition improved, and on the 10th day of admission, the patient was succeed extubated. At 12nd days of ICU admission, patient discharge from ICU. Discussion: Myasthenia and Cholinergic Crisis is a severe and life-threatening condition characterized by generalized muscle weakness with a respiratory compromise that requires ventilatory support. Respiratory failure may be present in the cholinergic crisis without cholinergic symptoms (miosis, diarrhea, urinary incontinence, bradycardia, emesis, lacrimation, or salivation). The most important management aspect of Myasthenia patients in crisis is the recognition and treatment of myasthenia vs cholinergic crisis.